Varstvo narave v Sloveniji in človek v igri dileme zapornikov skozi oči varstvoslovja - Žižek, Mateja (M. Žižek, 2017)
V opisani problematiki je torej ključno združevanje varstvoslovja z naravovarstvom, ki se v prvi vrsti ukvarja z varovanjem narave same, zaradi česar je predstavljena tudi kratka razvojna pot varstva narave v Sloveniji. Danes je varstvo narave in z njim življenjskega okolja v katerem živimo postalo družbena norma, urejena s pravnimi pravili in državno prisilo, z namenom zagotovitve pravic in dolžnosti, zato svoje mesto v diplomskem delu najdeta tudi zakonodaja in kazenskopravni sistem. Since the antiquity, security has been an essential element of human existence and development. Until recently, its idea was closely linked to traditional structures of war, defence and military assumptions. Nowadays, the overall character of modern security comprising all kinds of manifestations of social life is attributed to the level of social development, which was achieved in the 1990s. The Post-World War II period was particularly characterised by industrialisation and urbanisation, which expanded quickly. The following thesis is the result of modern civilisation discovery: fast development, fast population growth and universal production are causing horrific problems in the long term and hardly predictable consequences of environmental intervention. In the thesis, we tried to explain that the nature conservation scope is important for the conservation of endangered plant, animal species and beautiful landscapes it also concerns the measures that protect man and his health from the consequences of environmental intervention, which is frequently caused by man's recklessness. The thesis features man and nature as the subjects of »prisoner's dilemma« which is a game theory used in social science as a metaphor of rational decision-making in conflict situations between the two subjects. This theory shows the man who depends on nature and his activities in nature when the latter chooses between short-term needs and wishes and long-term consequences of his deeds. The introduction of arctic char in Double Lake is an illustrative example of this. The crucial element of the problem mentioned above is the integration of criminal justice and security with nature conservation of which primary concern is conservation of nature itself only. Hence, the thesis features a brief outline of nature conservation in Slovenia. Nowadays, nature and living environment conservation has become the legal norm imposed by the state the purpose of which is to ensure the rights and duties in the legislation and criminal law system.